Augmentation of protein-derived acetic acid production by heat-alkaline-induced changes in protein structure and conformation. (1st January 2016) - Wang, Xu; Li, Yanbo; Liu, Junxin; Ren, Nan-Qi; Qu, Jiuhui
Abstract: Waste-derived acetic acid (HAc) is an attractive feedstock for microbe-mediated biofuel production. However, fermentative conversion of HAc from waste-activated sludge (WAS) has low yield because of the high concentration of proteins not readily utilizable by microorganisms without prior hydrolysis. We investigated a combined technology for HAc augmentation during sludge protein fermentation. The maximal HAc yield increased over two-fold, reaching 0.502 ± 0.021 g/g protein (0.36 ± 0.01 g COD/g COD, ∼52% of the total volatile fatty acids) when synthetic sludge protein was heated at 120 °C for 30 min, treated at pH 12 for 24 h, and fermented at pH 9 for 72 h. Comprehensive analysis illustrated that the heat-alkaline pretreatment significantly induced protein fragmentation, simultaneously increasing the efficiency of protein biohydrolysis (from 35.5% to 85.9%) by inducing conformational changes indicative of protein unfolding. Consequently, the native α -helix content was decreased from 67.3% to 32.5% by conversion to an unordered shape, whose content increased from 27.5% to 45.5%; disulfide bonds were cleaved, whereas the main S–S stretching pattern was altered from gauche-gauche-gauche to gauche-gauche-trans, consequently causing increased protein susceptibility to proteolytic hydrolysis (76.3% vs. 47.0%). Economic analysis indicated that anaerobic fermentation with appropriate heat-alkaline pretreatment is a cost-effective approach for waste conversion to energy sources such as HAc. Graphical abstract: Highlights: The role of conditional stimulation on protein-based HAc formation was elucidated. The HAc yield increased over 2-fold with the studied augmentation strategy. The studied strategy importantly induced the protein fragmentation and denaturation. A synergistic effect of the protein transformations was observed on HAc augmentation. Economic analysis proved the feasibility of the strategy for waste-to-HAc conversion.